دور التسويق الإلكتروني في تنمية اتجاهات مستخدمي الإنترنت نحو المواقع السياحية في المملكة العربية السعودية - Al-teet, Ahmad; Nakhleh, Haithm (مجلة العلوم الإدارية و الإقتصادية, 2014)
The Internet has become just a vital part of the contemporary social life. It has gained importance in tourism sectors and institutions since it has served as a means to reach people who are interested and to influence their attitudes and behavior towards tourist sites. This research intended to identify the role of e-marketing in the developing attitudes of Internet users to tourist sites in Saudi Arabia. The research aimed also to explore the e-marketing mix: electronic service, cost, promotion, website, the accuracy of the information, payment, and personalization. The paper reviewed the previous studies of the electronic marketing of tourism, and worked on and developed a tool for field data collection which has given acceptable Validity and Reliability indicators. The research has been carried out with 478 participants (Internet users) chosen from various regions of the Kingdom. This paper presents methods to improve the role of e-marketing attitudes on Internet users in relation to tourism and through touching the needs and desires of tourists and its impact on the design of the website. The results of the research indicated that the level of using e-marketing towards the tourist sites in Saudi Arabia has increased, the attitudes of Internet users to tourist sites in Saudi Arabia were positive, and the dimensions of the e-marketing mix (e-service, price, promotion, website, the accuracy of the information, and payment) have impacted on Internet users’ attitudes towards the tourist sites in Saudi Arabia.